A Representational Approach to Executive Function Impairments in Young Adults with Down Syndrome. Issue 5 (3rd July 2020) - Iralde, Lydie; Roy, Arnaud; Detroy, Juliette; Allain, Philippe
ABSTRACT: Based on a representational perspective, this paper examines executive functioning in Down syndrome. Sixteen young adults with Down syndrome, 16 mental age- and 16 age-matched controls were compared on script sequencing and sorting tasks. Participants were asked to reestablish the sequential structure of script actions given with or without irrelevant actions. Impairments in script information processing were observed only in young adults with Down syndrome, who performed more slowly than controls, making mistakes in ordering actions, but rejecting aberrant elements. These data are consistent with the view that Down syndrome impairs the syntactic but not semantic dimension of script representation.